Female Board of Directors and Earnings Management: The Mediating Role of Profitability - Ria Karina; M Mardianto; Sri Wahyuni (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the influence of a female board of directors on earnings management. The mediating role of profitability was also studied to determine the influence of profitability in improving the relationship between the female board of directors and earnings management. The study was conducted on public companies listed in Indonesia Stock Exchange with a sample of 408 companies with annual report data from 810 Indonesian companies for 2018-2021 listed on IDX. The study used panel data regression with FEM (Fixed Effect Model) as the model to analyze the data using Eviews 12 application. The findings of this research indicate that female boards of directors do not influence earnings management. However, company profitability has a significant negative influence on the influence of a female board of directors on earnings management. Companies with more women on their board of directors tend to reduce earnings management practices when the company has good performance. This research provides practical implications for managers to consider gender equality in management. Studies regarding the role of profitability in moderating governance structure and earnings management are still rarely discussed. This research provides a theoretical contribution to the literature where a company's governance structure can influence earnings management practices depending on company performance.